EARLY RESPONSE OF LOCAL STEROID INJECTION VERSUS MINI INCISION TECHNIQUE IN TREATMENT OF CARPAL TUNNEL SYNDROME - Saboor, Abdus; Khan, Alamzeb; Afridi, Sikandar Aziz; Khan, Inam Ullah; Bhatti, Sajid Nazir; Ahmed, Ehtisham; Muhammad, Gul; Khan, Rao Suhail; Sultan, Shahid; Lodhi, Fahad Saqib (Journal of Ayub Medical College Abbottabad, 2015)
Background: Carpal tunnel syndrome (CTS) is one of the commonest peripheral neuropathies which effects mainly middle aged women. Different techniques are being tried to decrease the post-operative pain in patients operated for CTS. The objective of this study was to compare effectiveness of local injection of steroid and mini incision technique in the treatment of carpal tunnel syndrome. Methods: This randomized control trial was conducted at department of Orthopedics and department of Neurosurgery, Ayub Teaching Hospital, Abbottabad from Aug 2011 to Feb 2013. A total of 116 patients of CTS were randomly allocated to either of the two groups.58 Patient in Group A were subjected to local steroid injection and the same number of patient in Group B underwent mini incision technique. All patients of were advised to report to the OPD after one month to determine intervention effectiveness in terms of improvement in at least one grade of pain. Results: In this study mean age of the patients was 32.8±5.1 years. Female gender was in dominance with 99 (86.3%) cases. In this study we compared the effectiveness of local steroid injection and mini incision technique in the treatment of carpel tunnel syndrome. We found out that the steroid injection was effective in 69.0% cases while mini incision technique was effective in 56.9% cases. The difference being statistically insignificant with a p-value of 0.17. Conclusion: The difference in pain after 1 month of the intervention was not statistically significant. Keywords: Carpal tunnel syndrome, neuropathy, nerve compression syndromes